PENGARUH KOMPETENSI INTERNAL AUDITOR TEHADAP IMPLEMENTASI GOOD CORPORATE GOVERNANCE: (Survei Pada Bank Muamalat Kota Ambon) - Abdullah Sanduan (Jurnal Administrasi Terapan, 2026)
This study aims to determine and analyze whether there is an influence of internal auditor competency on the implementation of good corporate governance. This research uses a descriptive analysis method. The study was conducted at the branch office of Bank Muamalat in Ambon City. Data analysis and hypothesis testing used a simple linear regression analysis model to analyze the partial influence on the implementation of good corporate governance at the Bank Muamalat branch office in Ambon City.. The analysis model used to test the hypothesis is quantitative analysis in the form of sampling. This analysis is based on data from 38 managers and all employees of Bank Muamalat Ambon City branch through the distribution of questionnaires.The results of the research and hypothesis testing show that the competence of internal auditors partially has a positive and significant effect on the implementation of good corporate governance at the Bank Muamalat branch in Ambon City. The magnitude of the effect is 77.4%, and the level of influence is at a good level.Keyword : Good corporate governance, internal auditors, competency.